Experimental study of fatigue crack growth in raw and annealed pure copper with considering cyclic plastic effects. (April 2018) - Seifi, Rahman; Hosseini, Reza
Highlights: Fatigue crack growth rate calculations based on the Δ J are more accurate. Annealed samples have larger J-integral in comparison with raw material. Using the cyclic stress-strain curve gives accurate J-integral. Abstract: Some material, such as copper indicates hardening behavior under cyclic loading. Linear elastic fracture mechanics can be applied for low loads that the plastic zone size is small in compare with specimen dimensions. However, the cyclic J integral depends on the cyclic plastic response, therefore in ductile materials, the elastic plastic fracture mechanics based on the cyclic J integral justify fracture parameters better than the linear elastic fracture mechanics in various loadings. In this paper, for the cyclic loading in various loading conditions, crack growth behavior of copper with 99.9% purity was studied. For evaluation and comparison of the cyclic plastic behavior effects on the fatigue crack growth, some specimens were annealed in thermal furnace under420 °C for 35 min. With symmetric strain-controlled loadings, hysteresis loops were obtained for annealed and raw specimens. For studying of the fatigue crack growth rates, two important parameters as Δ K (stress intensity range) and Δ J (J-integral range) are evaluated. Crack growth parameters such as the fatigue life, crack growth rate and constants of Paris law and Dowling equation were investigated. Results revealed that in the same loading ranges, if growth rate is expressed versus Δ K, Paris law parameters are dependent to the load ratio, R while in representation versus Δ J, these parameters are almost constant. Also, the fatigue crack growth rate calculations based on the Δ J in materials such as annealed copper that has important hardening behavior, are more accurate.